2018
DOI: 10.1186/s12931-018-0940-7
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic lymphocytes in COPD airways: increased NK cells associated with disease, iNKT and NKT-like cells with current smoking

Abstract: BackgroundCytotoxic lymphocytes are increased in the airways of COPD patients. Whether this increase is driven primarily by the disease or by smoking is not clear, nor whether it correlates with the rate of decline in lung function.MethodsBronchoscopy with BAL was performed in 52 subjects recruited from the longitudinal OLIN COPD study according to pre-determined criteria; 12 with COPD and a rapid decline in lung function (loss of FEV1 ≥ 60 ml/year), 10 with COPD and a non-rapid decline in lung function (loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…The converse trends between the blood and BAL were also seen with respect to CD4 + cells in a patient study of smokers with COPD. Smoking was found to increase the number of CD8 + T cells and CD8 + NKT-like cells in the BAL of COPD patients with a concurrent reduction of CD4 + cells in the BAL and increase of CD4 + in the blood as previously reported (120, 121), while another study found an increase in iNKT and NKT-like cells in BAL fluid from current smokers but not COPD patients (121). Indeed, the role of iNKT cells in COPD may more relate to exacerbations, which can be caused by infection with respiratory viruses and other pathogens.…”
Section: Role Of Unconventional T Cells In Chronic Lung Disorderssupporting
confidence: 79%
“…The converse trends between the blood and BAL were also seen with respect to CD4 + cells in a patient study of smokers with COPD. Smoking was found to increase the number of CD8 + T cells and CD8 + NKT-like cells in the BAL of COPD patients with a concurrent reduction of CD4 + cells in the BAL and increase of CD4 + in the blood as previously reported (120, 121), while another study found an increase in iNKT and NKT-like cells in BAL fluid from current smokers but not COPD patients (121). Indeed, the role of iNKT cells in COPD may more relate to exacerbations, which can be caused by infection with respiratory viruses and other pathogens.…”
Section: Role Of Unconventional T Cells In Chronic Lung Disorderssupporting
confidence: 79%
“…Focusing on regulatory immune cells, the aim was to assess the distribution of Tregs in COPD in general and its association with disease status, smoking status and rapid/non-rapid decline in LF in particular. Findings related to cytotoxic immune cells have been reported previously [ 4 ].…”
Section: Introductionsupporting
confidence: 63%
“…Macrophages are thought to play a major role as they can release matrix metalloproteinases capable of degrading the extracellular matrix in the lungs, as well as secrete chemokines that attract other immune cells such as monocytes and lymphocytes. In the latter population, the balance in COPD airways is tipped towards cytotoxic cell types such as CD8 + T cells [ 3 ] and NK cells [ 4 ]. Among regulatory immune cells, regulatory T cells (Tregs) are thought to be a key player, particularly in protecting the body from an over activated immune response [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Airway damage in COPD is triggered by dust, fumes, vapors, or gas, but the primary factor is exposure to tobacco smoke ( 23 ). Cigarette smoke alters both innate and adaptive immunity by upregulating cytokines (IL-1, IL-6, IL-8, tumor necrosis factor [TNF]-α…) ( 24 , 25 ), and modifying the physiological function of alveolar macrophages ( 26 ), dendritic cells ( 27 ), neutrophils ( 28 ), and natural killer cells ( 29 ). Smoking also modifies the behavior of the epithelium by increasing mucin production (MUC5AC) ( 30 ) and disrupting epithelial cell-cell junctions, thus increasing the permeability of the epithelial barrier ( 31 ).…”
Section: Pathophysiology Of Asthma and Copdmentioning
confidence: 99%